Casing design theory and practice - Rahman, S. S.; Chilingar, George V., 1929- (Developments in petroleum science, 1995)
Casing design has followed an evolutionary trend and most improvements have been made due to the advancement of technology. Contributions to the technology in casing design have come from fundamental research and field tests, which have made casing safe and economical. This book gathers together much available information in the subject area and shows how it may be used in deciding the best procedure for casing design i.e. optimizing casing design for deriving maximum profit from a particular well. The problems and their solutions, which are provided in each chapter, and the computer program (3.5 in. disk) are intended to serve two purposes:- firstly, as illustrations for students and practicing engineers to understand the subject matter, and secondly, to enable them to optimize casing design for a wide range of wells to be drilled in the future.